Prepare : Student's Book - Styring James (Cambridge University Press, 2015)
PREPARE 2nd Edition Level 4 combines topics of interest to youth with step-by-step preparation for the revised Pre-2020 Exam, allowing students to use topics and resources tailored to their interests. Surname. You can enjoy personalized and interactive lessons. The new Life Skills approach combines insights from the Cambridge Life Skills Framework to encourage learners to broaden their horizons and knowledge. Teachers can rest easy knowing that each lesson will help their students pass their exams and that the advanced grammar and vocabulary curriculum will help students use English with confidence. Access student eBooks online with interactive audio and video on Cambridge One.